2009
DOI: 10.1007/s12664-009-0087-z
|View full text |Cite
|
Sign up to set email alerts
|

Colorectal cancer distribution in 220 Indian patients undergoing colonoscopy

Abstract: Almost one-third of the colorectal cancers in this series occurred in the seventh decade and were located distal to the splenic flexure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
26
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(42 citation statements)
references
References 25 publications
(29 reference statements)
13
26
0
1
Order By: Relevance
“…Peedikayil et al also found most of the tumors distal to the splenic flexure. [8] In agreement with our study, Musthafa et al saw an overall proximal migration of CRC. [8] Also in the West a shift of tumor location to proximal parts of the colon is observed.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Peedikayil et al also found most of the tumors distal to the splenic flexure. [8] In agreement with our study, Musthafa et al saw an overall proximal migration of CRC. [8] Also in the West a shift of tumor location to proximal parts of the colon is observed.…”
Section: Discussionsupporting
confidence: 93%
“…[8] In agreement with our study, Musthafa et al saw an overall proximal migration of CRC. [8] Also in the West a shift of tumor location to proximal parts of the colon is observed. [14] This trend has been noticed also in Asian countries like Korea and Japan.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Majority of polyps found in their study were adenomatous. Peedikayil et al (2009) have studied the colon cancer distribution within the colon and have done the analysis on retrospective data. They conclude that colon cancer DOI:http://dx.doi.org/10.7314/APJCP.2014.15.13.5111 Feasibility of CT Colonography as a Diagnostic Procedure in Colon Cancer Screening in India distribution was more in the descending colon and the rectosigmoid junction.…”
Section: Global and India Scenario Of Colon Cancersmentioning
confidence: 99%